Identification of Missense ADGRV1 Mutation as a Candidate Genetic Cause of Familial Febrile Seizure 4 - Ji Yoon Han; Hyun Joo Lee; Young-Mock Lee; Joonhong Park (Children, 2020)
Febrile seizure (FS) is related to a febrile illness (temperature > 38 °C) not caused by an infection of central nervous system, without neurologic deficits in children aged 6–60 months. The family study implied a polygenic model in the families of proband(s) with single FS, however in families with repeated FS, inheritance was matched to autosomal dominance with reduced disease penetrance. A 20 month-old girl showed recurrent FS and afebrile seizures without developmental delay or intellectual disability. The seizures disappeared after 60 months without anti-seizure medication. The 35 year-old proband’s mother also experienced five episodes of simple FS and two episodes of unprovoked seizures before 5 years old. Targeted exome sequencing was conducted along with epilepsy/seizure-associated gene-filtering to identify the candidate causative mutation. As a result, a heterozygous c.2039A>G of the ADGRV1 gene leading to a codon change of aspartic acid to glycine at the position 680 (rs547076322) was identified. This protein’s glycine residue is highly conserved, and its allele frequency is 0.00002827 in the gnomAD population database. ADGRV1 mutation may have an influential role in the occurrence of genetic epilepsies, especially those with febrile and afebrile seizures. Further investigation of ADGRV1 mutations is needed to prove that it is a significant susceptible gene for febrile and/or afebrile seizures in early childhood.